Informação e atividade bancária local: evidências a partir de medidas de tempo e distância - Thiago Antonio Pastorelli Rodrigues (2013)
Financial intermediaries arise as a result of comparative advantage in the production of proprietary information. Therefore, they are able to reduce information asymmetries in favor of customers and identify potential borrowers, industries and regions with a high return probability. In this sense, this study aims to find evidences of the relation between information and banking activity. This relation is defined empirically by measures of time and distance associated with the location of bank branches. The measures are constructed from Brazilian data, aggregated at the market-level, where the relevant extent is the municipality. The results show that time and distance matter in determining the local availability of credit and suggest that the reduction of information asymmetries is the channel through which these dimensions influence the credit offered in the municipalities. Additionally, the results indicate that the geographic distribution, the organizational structure and the local characteristics of the banking system may change the incentives of banking staff to produce information.